Activation of the phosphatidylinositol 3‐kinase pathway plays important roles in reduction of cerebral infarction by cilnidipine. (31st August 2015) - Son, Jeong‐Woo; Choi, Hojin; Yoo, Arum; Park, Hyun‐Hee; Kim, Young‐Seo; Lee, Kyu‐Yong; Lee, Young Joo; Koh, Seong‐Ho
Abstract: Cerebral infarction causes permanent neuronal loss inducing severe morbidity and mortality. Because hypertension is the main risk factor for cerebral infarction and most patients with hypertension take antihypertensive drugs daily, the neuroprotective effects and mechanisms of anti‐hypertensive drugs need to be investigated. Cilnidipine, a long‐acting, new generation 1, 4‐dihydropyridine inhibitor of both L‐ and N‐type calcium channels, was reported to reduce oxidative stress. In this study, we investigated whether cilnidipine has therapeutic effects in an animal model of cerebral infarction. After determination of the most effective dose of cilnidipine, a total of 128 rats were subjected to middle cerebral artery occlusion. Neurobehavioral function test and brain MRI were performed, and rats with similar sized infarcts were randomized to either the cilnidipine group or the control group. Cilnidipine treatment was performed with reperfusion after 2‐h occlusion. Western blots and immunohistochemistry were also performed after 24‐h occlusion. Initial infarct volume on diffusion‐weighted MRI was not different between the cilnidipine group and the control group; however, fluid‐attenuated inversion recovery MRI at 24 h showed significantly reduced infarct volume in the cilnidipine group compared with the control group. Cilnidipine treatment significantly decreased the number of triphosphate nick end labeling‐positive cells compared to the control group. Western blot and immunohistochemistry showed increased expression of phosphorylated Akt (Ser473), phosphorylated glycogen synthase kinase‐3β, and Bcl‐2 and decreased expression of Bax and cleaved caspase‐3. These results suggest that cilnidipine, which is used for the treatment of hypertension, has neuroprotective effects in the ischemic brain through activation of the PI3K pathway. We investigated whether cilnidipine has neuroprotective effects on ischemic stroke in an animal model. We have demonstrated that the neuroprotective effect of cilnidipine is associated with the activation of the PI3K pathway. Considering the daily use of antihypertensive drugs for patients with hypertension, cilnidipine could be beneficial for patients with ischemic stroke. Abstract : We investigated whether cilnidipine has neuroprotective effects on ischemic stroke in an animal model. We have demonstrated that the neuroprotective effect of cilnidipine is associated with the activation of the PI3K pathway. Considering the daily use of antihypertensive drugs for patients with hypertension, cilnidipine could be beneficial for patients with ischemic stroke.